Investigation of the Essential and Non-essential Element Contents of Some Aromatic Coffees and Effect of Sugar Addition - Uygunoz, Deniz; Fercan, Melek Merve; Kipcak, Azmi Seyhun; Derun, Emek Moroydor (BENTHAM SCIENCE PUBL LTD, 2026)
Introduction In this study, the contents of essential and non-essential elements in the sugary and sugar-free varieties of aromatic coffees produced in Turkey were decided, and the effect of sugar addition was examined.Methods For this purpose, essential (Mg, Se, B, Na, Ca, K, Co, Cr, Fe, Cu, Mn, Mo, P and Zn) and non-essential (As, Ba, Al, Cd, Ti, Ni, Sb and Pb) element contents of the aromatic coffees (sugary and sugar-free) (Classic, Gum Mastic, Gum Mastic Turkish Coffee, Hazelnut, Caramel and Turkish Coffee) supplied from a single brand were detected by using ICP-OES. The effects of the elements taken into the body by the consumption of coffee varieties on health and how much of an individual's daily requirements are met were investigated. Thus, the place and importance of coffee consumption in nutrition have been determined. For coffee consumption of 3 cups, the intake amounts of selected elements were calculated. Furthermore, a risk assessment study was performed by utilizing the non-essential element concentrations of selected coffees.Results Experimental results showed that K is the most ample essential element in all types of coffee, and it has been proven that K ingestion encounters the daily requirement of 1% to 2% for adults.Conclusion According to the risk assessment results, the hazard index was calculated for 3 cups of each coffee type intake as less than 1, and these coffees may be classified in the low-risk group.
Keywords: Aromatic coffee; essential and non-essential elements; ICP-OES; sugar effect; carcinogenic risk; non-carcinogenic risk; LEMON; ORIGIN; BEANS; Chemistry